FUNDAMENTAL RIGHTS, GENERALIZABLE INTERESTS, AND HUMAN NEEDS (Andamios, Revista de Investigación Social, 2008)
The objective is to contribute to the discussion of Cristina Lafont’s notion of political legitimacy, emphasizing its realism—not constructivism—as understood in Jürgen Habermas’ discursive ethics. The author argues that legitimacy is usually associated with decisionmaking procedures but is not identical to mere agreement per se. Legitimacy incorporates the idea of the general interest as a practical presupposition. These interests are defined as fundamental rights in the procedure. The notion of justice in this sense is a contextual one, but capable of transcending historical agreements and susceptible to revision in terms of truth.
Keywords: Legitimacy; justice; fundamental rights; interests; discourse ethics